Analisis Dampak Pembangunan Jalan Terhadap Pertumbuhan Usaha Ekonomi Rakyat Di Pedalaman May Brat Provinsi Papua Barat (Studi Kasus Di Distrik Ayamaru, Aitinyo Dan Aifat) - Iek, Mesak (Jurnal Ekonomi Kuantitatif Terapan, 2013)
This research aims to analyzing the impact of road construction on the growth of people’s economic business, people’s income, the social and economic benefit got by society in remote areas of  May Barat Regency, located in the districts of Ayamaru, Aitinyo, and Aifiat. The research’s samples were people who having or running their own business, which was selected based on the tribe’s homogeneity and the earning for living ways of people,  and selected using purposive sampling targeting. Quesionair and Focus Group Discussion (FGD) were conducted in collected datas, the analysis tools for this research were using the test of income average gaps and SEM Analysis. The results of this research showed that the road and bridge construction has positive impact on the society’s economic business income, and the social benefit gave more impact than the economic benefit, it was proven by loading factor values (LF=l) X à Y1 dan X à Y2, 0,540 for the economic benefit  and 0,683 for the social benefit.  In order to give more long term multiplier benefit for the society, the constructed Sorong-Mai Brat infrastructure needs to be improved by the goverment.
Keywords: Road construction; economic business; business economic improvement; income of society